2007
DOI: 10.1016/j.neuroscience.2006.12.037
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase inhibitor SP600125 modulates the period of mammalian circadian rhythms

Abstract: Circadian rhythms are endogenous cycles with periods close to, but not exactly equal to, 24 h. In mammals, circadian rhythms are generated in the suprachiasmatic nucleus (SCN) of the hypothalamus as well as several peripheral cell types, such as fibroblasts. Protein kinases are key regulators of the circadian molecular machinery. We investigated the role of the c-Jun N-terminal kinases (JNK), which belong to the mitogen-activated protein kinases family, in the regulation of circadian rhythms. In rat-1 fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 61 publications
4
45
0
Order By: Relevance
“…In a previous study, we have shown that SP600125, an inhibitor of one of the mitogen-activated protein kinases (MAPKs) c-Jun N-terminal kinase (JNK), similarly extends period in fibroblasts and the mouse SCN (Chansard et al, 2007). In addition, valproic acid shortens the period in rat-1 fibroblasts (Chansard et al, 2007). These results further suggest that peripheral cell models have a potential to allow us to study the effects of chemicals on circadian rhythm generation.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…In a previous study, we have shown that SP600125, an inhibitor of one of the mitogen-activated protein kinases (MAPKs) c-Jun N-terminal kinase (JNK), similarly extends period in fibroblasts and the mouse SCN (Chansard et al, 2007). In addition, valproic acid shortens the period in rat-1 fibroblasts (Chansard et al, 2007). These results further suggest that peripheral cell models have a potential to allow us to study the effects of chemicals on circadian rhythm generation.…”
Section: Introductionmentioning
confidence: 88%
“…Detailed procedures are described in the previous study (Chansard et al, 2007). In brief, 3 days before starting experiments, 10 6 rat-1 fibroblasts, stably transfected with Period1-luciferase reporter gene ( [Izumo et al, 2003], generous gift from Carl Johnson, Vanderbilt University, Nashville, TN, USA), were seeded in a 35 mm Petri dish.…”
Section: Rat-1 Fibroblasts Culturementioning
confidence: 99%
See 3 more Smart Citations